2008
DOI: 10.1074/jbc.m803037200
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide Inhibits L-type Ca2+ Channels via Redox Modulation of Key Cysteine Residues by Mitochondrial Reactive Oxygen Species

Abstract: Conditions of stress, such as myocardial infarction, stimulate up-regulation of heme oxygenase (HO-1) to provide cardioprotection. Here, we show that CO, a product of heme catabolism by HO-1, directly inhibits native rat cardiomyocyte L-type Ca 2؉ currents and the recombinant ␣ 1C subunit of the human cardiac L-type Ca 2؉ channel. CO (applied via a recognized CO donor molecule or as the dissolved gas) caused reversible, voltage-independent channel inhibition, which was dependent on the presence of a spliced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(124 citation statements)
references
References 41 publications
4
120
0
Order By: Relevance
“…3d) and found that complex I inhibition was without effect on P2X4 currents or their modulation by CORM-2. Similarly, inhibition of the complex III Q o site, which would be expected to decrease cytosolic ROS [38] and has been shown to block the CORM-2 inhibition of L-type calcium channels [29], had no effect on P2X4 currents or their inhibition by CORM-2. Results obtained with the complex III inhibitor, antimycin A, were intriguing.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…3d) and found that complex I inhibition was without effect on P2X4 currents or their modulation by CORM-2. Similarly, inhibition of the complex III Q o site, which would be expected to decrease cytosolic ROS [38] and has been shown to block the CORM-2 inhibition of L-type calcium channels [29], had no effect on P2X4 currents or their inhibition by CORM-2. Results obtained with the complex III inhibitor, antimycin A, were intriguing.…”
Section: Discussionmentioning
confidence: 97%
“…This is the proposed mechanism by which CO and CORM-2 exert an inhibitory effect on L-type calcium channels [29]. Incubation of cells with 100 μM KCN, which would also inhibit complex IV, did not mimic the inhibitory effect of CORM-2, and we found that the inclusion of reducing (DTT) or oxidising (H 2 O 2 ) agents in the patch pipette had no effect on the ability of CORM-2 to inhibit P2X4 currents (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations